Methods Of Using Modern Pedagogical Technologies In Education - Zuhra Abdurahmonovna Umarova (Euro Asian Journal Publishing, 2023)
This article describes the problems of modern pedagogical technologies in education. In this case, the didactic structure of the educational process makes it possible to distinguish the following pedagogical technologies: pedagogical technology based on the creation of factors that lead to the fulfillment of certain educational goals (in the future, the technology of creating educational factors), ideas about pedagogical technology based on activity given
Keywords: modern pedagogical technologies in education; educational process; didactic content; pedagogical technologies